Editorial: ETHICAL CONCERNS REGARDING CLINICAL EXPERIMENTS ON PATIENTS WHO ARE NOT ABLE TO CONSENT - ALUAȘ, Maria (Studia Universitatis Babeş-Bolyai Bioethica, 2017)
This new issue of Studia Universitatis Babeș-Bolyai – Bioethica is a mix of topics from different medical research area: dental medicine, medical student’s issues, patient’s rights, organ transplantations, and ecological economy. All papers present complex issues and approaches related to different area of thinking Ethics. As a conclusion we can say that Ethics is always very challenging and new.